2022
DOI: 10.37287/ijghr.v4i1.784
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Mental Health Problems Health Personnel During Covid-19 Pandemic

Abstract: The determination of the pandemic condition by WHO has caused various public responses and psychosocial problems. This research is important because the spread of the virus is very fast, widespread and mass causes cases to increase and have an impact not only on physical but also psychological conditions, causing mental health problems. Various efforts have been made by the government to combat the epidemic, community participation involving individuals, families and community groups is urgently needed to solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…The disorders found in this study were similar to those found in study conducted during the COVID‐19 pandemic (Iskandarsyah et al., 2021 ; Marthoenis et al., 2021 ; Sunjaya et al., 2021 ). However, the prevalences were skewed—much higher in hospitals providing care for patients with COVID‐19 and lower in non‐COVID‐19 healthcare facilities (Rochmawati et al., 2022 ; Sofiani et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The disorders found in this study were similar to those found in study conducted during the COVID‐19 pandemic (Iskandarsyah et al., 2021 ; Marthoenis et al., 2021 ; Sunjaya et al., 2021 ). However, the prevalences were skewed—much higher in hospitals providing care for patients with COVID‐19 and lower in non‐COVID‐19 healthcare facilities (Rochmawati et al., 2022 ; Sofiani et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hasil deteksi dini sebagai upaya preventif atau pencegahan dalam Kesehatan jiwa sehingga dapat menemukan akar permasalahan lebih cepat dan penanganan yang segera sebelum menjadi masalah aktual gangguan jiwa (Mariyati et al, 2021). Fenomena tersebut tak lepas dari adanya setengah dari semua gangguan mental dimulai pada usia 14 tahun dan biasanya didahului oleh gangguan psikososial non-spesifik yang berpotensi berkembang pada gangguan mental utama dan menyumbang 45% dari beban penyakit global pada rentang usia 0-25 tahun (Rochmawati et al, 2022).…”
Section: Hasil Dan Pembahasanunclassified
“…Peningkatan pengetahuan kader jiwa juga merupakan indikator pencapaian yang akan dicapai dalam pengabdian kepada masyarakat melalui edukasi dan role play kepada masyarakat ini. Hal ini juga didukung dengan pendidikan Kesehatan jiwa untuk mengidentifikasi secara dini gangguan jiwa dapat meningkatkan pengetahuan kader (Febriyanto, PH & Indrayanti, 2019); (Rochmawati et al, 2022). Pelatihan kader Kesehatan jiwa juga yang baru maupun lama juga perlu ditingkatkan walaupun lokasi tersebut sudah dilakukan karena adanya penyegaran dan meningkatkan ilmu dan metode yang update.…”
Section: Hasil Dan Pembahasanunclassified